Konsep Metafora Architecture Pada Perancangan Pusat Sentra Kuliner Jagung Di Kabupaten Takalar - Asyifah Man, Nur; Amin, Burhanuddin; Rahmani, Ahmad Ibrahim (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2023)
Indonesia is an agricultural country where one of the primary commodities is the farm sector. Corn is one of Sulawesi's leading food crop commodities, especially South Sulawesi. The region that is one of the best maize producers in South Sulawesi is Takalar Regency. Therefore, this sector must be able to be developed to help the regional economy. The general objective of this discussion is to design a corn culinary center tour in Takalar Regency with a metaphorical architectural approach. The research methods used are literature, precedent, and field studies: site Selection Criteria, Location Allocation, Land Area, Access to the Site, and Utilities. The location chosen for the corn culinary tourism design is in Polongbangkeng Utara District. The results of the field data analysis show that Palleko Village is a strategic Village from the several primary considerations above. The environmental conditions on the site are a strategic area of the Regency as a center for artificial tourism, especially culinary tourism. Therefore, to optimize the tourism potential of culinary centers in Takalar Regency by developing one of the food crop sectors in the form of corn, it is necessary to design a corn culinary tourism center with a metaphorical architectural approach in Takalar Regency, which can be an attractive culinary tourism option for the community and is more organized in offering food processed corn centrally.